Physicochemical, nutritional and oxalate concentration of taro tubers grown in North Sumatera, Indonesia: effect of blanching and cooking treatments. - Mansoor, A. H.; Martony, O.; Yeap, C. H.; Tan, C. M.; Wong, V. K. Y.; Cheong, J. H.; Sii, B. C. S.; Ivy, C. (International Journal of Agricultural Technology, 2025)
The presence of anti-nutrients is considered unfavourable to consumers as they limit the utilization of nutrients present in foods when eaten by the consumers. Oxalate is among the most common anti-nutrients found in many agricultural products. This study investigated the effects of soaking in sodium chloride (NaCl) solution and boiling treatment on the physicochemical properties, nutrients and oxalate content in taro tuber samples grown in North Sumatera, Indonesia. The data showed that the physicochemical properties (colour and pH) of the samples were not significantly impacted by both treatments. From the aspect of proximate compositions, soaked samples did not vary significantly from the control. On the other hand, noticeable drop in the ash, protein, fat and fibre contents were observed in the boiled samples. Both soaked and boiled samples recorded higher carbohydrate contents than the corresponding control. The treatments led to a loss of 29.69% to 99.23% of total oxalates in the samples, with boiling treatment exhibiting the greatest effect. Moreover, both treatments showed positive correlation with the concentration of salt and treatment duration, where a higher concentration of NaCl and a longer duration resulted in a higher loss of oxalate. However, only T4 could be regarded as low-oxalate content Thus, further treatments need to be considered to lower the amount to a greater extent.